1996
DOI: 10.1093/ndt/11.6.1043
|View full text |Cite
|
Sign up to set email alerts
|

IgA nephropathy in patients over 50 years of age: a multicentre, prospective study

Abstract: When the histological diagnosis of IgAN was established, factors that carry a poor prognosis, i.e. proteinuria, high blood pressure, and decreased Ccr were more commonly present in patients over 50 than under 50. However, after the completion of a relatively short follow-up period, renal survival was identical in the two study groups. Prolonged follow-up is necessary to confirm this trend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
14
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 14 publications
6
14
0
Order By: Relevance
“…Clinicopathological features and outcomes of primary IgA nephropathy (IgAN) in the elderly population (>65 years old) have not been adequately evaluated. In a recent meta‐analysis gathering all searchable data, from 1980 to 2010, only nine studies of reasonable quality included elderly patients (four from Japan, one from France, one from Iran, one from Italy, one from Spain and one from China) . Among the nine studies, only a minority (<5%) of patients were elderly (age >50 or >65 years).…”
mentioning
confidence: 99%
“…Clinicopathological features and outcomes of primary IgA nephropathy (IgAN) in the elderly population (>65 years old) have not been adequately evaluated. In a recent meta‐analysis gathering all searchable data, from 1980 to 2010, only nine studies of reasonable quality included elderly patients (four from Japan, one from France, one from Iran, one from Italy, one from Spain and one from China) . Among the nine studies, only a minority (<5%) of patients were elderly (age >50 or >65 years).…”
mentioning
confidence: 99%
“…Many literature sources suggest that age is also a prognostic factor, and old age is correlated with poor prognosis [28, 29]. A previous study compared patients of different ages (≥ 50 and <50 years old) and found a higher incidence of arterial intimal thickening in the elder group, but no differences in the degree of other pathological changes; the follow-up for 41 months showed no difference in survival [30]. …”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in a 2012 meta‐analysis, showing only nine studies in the past three decades containing elderly patients . Only one of the nine studies was designed to evaluate IgA nephropathy in the elderly (aged ≥50 years), and of the 33 patients in that study, only 16 had limited histological information …”
Section: Iga Nephropathy In Elderly Patientsmentioning
confidence: 99%
“…33 Only one of the nine studies was designed to evaluate IgA nephropathy in the elderly (aged ≥50 years), and of the 33 patients in that study, only 16 had limited histological information. 34 A total of four publications have since been added to the literature (searchable and in English). They are discussed below and summarized in Table 1.…”
Section: Iga Nephropathy In Elderly Patientsmentioning
confidence: 99%
See 1 more Smart Citation